2009
DOI: 10.1007/s10265-009-0220-1
|View full text |Cite
|
Sign up to set email alerts
|

Clonal identification by microsatellite loci in sporadic flowering of a dwarf bamboo species, Sasa cernua

Abstract: Dwarf bamboo species are monocarpic. They flower simultaneously and die after several decades. The type of flowering in the genus Sasa ranges from sporadic to gregarious. In order to determine whether or not the sporadic flowering of dwarf bamboo is fixed genetically, we investigated the distribution of clones using eight microsatellite (SSR) loci in a sporadic flowering patch of Sasa cernua Makino, a major dwarf bamboo species found in central Hokkaido. In May 2006, flowering occurred on 60.5% of living culms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 11 publications
1
24
0
2
Order By: Relevance
“…Our previous study on small-scale flowering of a dwarf bamboo species, Sasa cernua MAKINO, revealed that the flowering assembly consisted of an identical genet (Kitamura and Kawahara 2009). Makita (1998) indicated in terms of evolutionary trends that sexual regeneration gives rise to inter-genet competition in the habitat and affects the life history processes of dwarf bamboos.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study on small-scale flowering of a dwarf bamboo species, Sasa cernua MAKINO, revealed that the flowering assembly consisted of an identical genet (Kitamura and Kawahara 2009). Makita (1998) indicated in terms of evolutionary trends that sexual regeneration gives rise to inter-genet competition in the habitat and affects the life history processes of dwarf bamboos.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of sexual reproduction, bamboos and dwarf bamboos are monocarpic (Janzen 1976;Kudoh and Ujiie 1990;Simmonds 1980) and take several decades to flower (Campbell 1985); thus, regeneration by seeds is a rare occurrence. Consequently, they persist for relatively long periods, often exceeding several decades, without any sexual reproduction and dominate the forest floor or once disturbed empty habitats by forming exclusive clonal aggregation (Kitamura and Kawahara 2009;Matsuo et al 2008;Suyama et al 2000). Notably, these previous genetic studies have revealed the existence of genetically variable genets in local populations (Kitamura and Kawahara 2009;Suyama et al 2000), indicating the primary role of sexual reproduction in retaining genetic diversity of dwarf bamboo species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable age at maturity is also found in many monocarpic plants, such as desert annuals (Venable 2007), Agave spp. (Nobel 1992), and many bamboos (Kitamura and Kawahara 2009). Many invertebrate species with diapausing eggs, such as Daphnia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, microsatellites are one of the robust classes of genetic tools, because microsatellite loci are highly polymorphic, codominant, and reproducible, and have recently been widely used (Edwards et al 2008, Kitamura andKawahara 2009).…”
mentioning
confidence: 99%